2018
DOI: 10.12968/bjon.2018.27.8.s4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged flushing interval in totally implantable venous access devices (TIVADs)

Abstract: Totally implantable venous access device (TIVAD) lumen occlusion is a long-term complication of central venous catheters, associated with risks of infection, therapy interruptions and increased healthcare costs. The role of flushing and locking in maintaining TIVAD patency is paramount. Most flushing protocols are based on manufacturers' recommendations, which indicate that 4 weeks is the safest interval between two consecutive flushing procedures during periods when TIVADs are not in use. Conversely, results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 16 publications
0
33
0
3
Order By: Relevance
“…However, as it did not make comparisons with shorter intervals, this report was unable to provide strong evidence of this safety. Another study conducted by Rasero L divided patients with ports into a short-term group (<45 days) and a long-term group (>45 days) according to the flushing interval, and as a result, found no significant difference in catheter occlusion incidence [ 16 ]. Unfortunately, the sample size was relatively small (less than 90 patients totally).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as it did not make comparisons with shorter intervals, this report was unable to provide strong evidence of this safety. Another study conducted by Rasero L divided patients with ports into a short-term group (<45 days) and a long-term group (>45 days) according to the flushing interval, and as a result, found no significant difference in catheter occlusion incidence [ 16 ]. Unfortunately, the sample size was relatively small (less than 90 patients totally).…”
Section: Discussionmentioning
confidence: 99%
“…For the flushing interval, most manufacturers indicate that flushing must be performed every 4 weeks when the device is not in use (i.e., during the off-treatment period) [ 14 ]. Meanwhile, several studies have shown that extended flushing intervals are safe [ 15 , 16 ]. In fact, in our outpatient setting, we found that some patients could not follow the 4-week interval strictly after the completion of treatment, but complications rarely occurred.…”
Section: Introductionmentioning
confidence: 99%
“…El grupo A donde el mantenimiento ocurrió en ≤ 45 días de intervalo y grupo B con > 45 días. Después del estudio retrospectivo, 7 pacientes que se encontraban en el grupo de intervalo ≤ 45 días presentaron complicaciones relacionadas con la obstrucción, mientras en el grupo de intervalo > 45 días no ocurrió ninguna complicación, sin embargo, no comprobó diferencia significativa durante el análisis (16) .…”
Section: Discusión Estrategias De Prevención De La Obstrucción En Cvc-tiunclassified
“…Por tanto, ninguna literatura encontrada constató significativa estadística que comprobó seguridad y efectividad relacionadas al tiempo de intervalo entre los mantenimientos. No obstante, se sabe que el aumento en el tiempo de intervalo reduce el acceso a ese dispositivo, con la consecuente reducción del riesgo de infección y de incomodidad para el paciente (16,17) .…”
Section: Discusión Estrategias De Prevención De La Obstrucción En Cvc-tiunclassified
“…Porém estudos têm demonstrando que a extensão deste intervalo para a realização do Locking é eficaz e seguro na manutenção da permeabilidade. Estudo recente corrobora com os anteriores onde não observou diferença entre o curto e o longo período no intervalo do Locking com taxa de complicações quando o cateter está em uso intermitente 19,20 .…”
Section: Cuidados Na Manutenção Da Permeabilidade Dos Davcunclassified